2020
DOI: 10.3892/ijo.2020.5007
|View full text |Cite
|
Sign up to set email alerts
|

ADAM12 silencing promotes cellular apoptosis by activating autophagy in choriocarcinoma cells

Abstract: ADAM metallopeptidase domain 12 (ADAM12) has been demonstrated to mediate cell proliferation and apoptosis resistance in several types of cancer cells. However, the effect of ADAM12 silencing on the proliferation and apoptosis of choriocarcinoma cells remains unknown. The present study revealed that ADAM12 silencing significantly inhibited cellular activity and proliferation in the human choriocarcinoma JEG3 cell line and increased the rate of apoptosis. In addition, ADAM12 silencing significantly increased th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 82 publications
0
7
0
Order By: Relevance
“…Several genes have also been reported to play an oncogene role in choriocarcinoma cells. Wang et al have certified that ADAM1 depletion facilitates choriocarcinoma cell apoptosis via activating autophagy [ 15 ]. Zhao et al have found that aberrantly expressed SALL4 facilitates choriocarcinoma cell proliferation through the β -catenin/c-Myc pathway [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several genes have also been reported to play an oncogene role in choriocarcinoma cells. Wang et al have certified that ADAM1 depletion facilitates choriocarcinoma cell apoptosis via activating autophagy [ 15 ]. Zhao et al have found that aberrantly expressed SALL4 facilitates choriocarcinoma cell proliferation through the β -catenin/c-Myc pathway [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Because it has been demonstrated that ADAM12 mediates cell proliferation through the activation of the PI3K/Akt/mTOR pathway, which is involved in several cellular functions and often contributes to oncogenesis [ 46 , 47 ], the phosphorylation levels of Akt ( Figure 6 A) and mTOR ( Figure 6 B) were investigated [ 48 ]. As shown in Figure 6 A, the treatment of 48 h with both concentrations of VNZ (100 nM or 1 µM) induced a significant increase in phospho-Akt (p-Akt) as compared to the VH group.…”
Section: Resultsmentioning
confidence: 99%
“…ADAM12 expression was previously reported to be high in breast, oesophageal, pituitary tumor, and choriocarcinoma [16,17,39] . Huang et al [16] found that lnc015192 competitively binds to miR-34a through sponging activity, inhibiting ADAM12 expression as well as tumour cell invasion, metastasis and the epithelial-to-mesenchymal transition.…”
Section: Discussionmentioning
confidence: 99%